A Fluoride‐Free and Super‐Wetting Functionalized‐Material with pH‐Responsiveness for Controllable Separation of Multiphase Oil/Water Mixtures. Issue 2 (28th October 2020) - Qu, Mengnan; Liu, Lulu; Yang, Xin; Yang, Chen; Li, Jiehui; Liu, Qian; Peng, Lei; Liu, Xiangrong; He, Jinmei
Abstract : Nowadays, oily wastewater seriously endangers human health and living environment. Intelligent materials with switchable wettability gear up the broad application prospect in controllable oil/water separation and have received extensive attention. Herein, a simple and novel fluoride‐free method for preparing pH‐responsive super‐wetting material by monomer polymerization is reported. Surprisingly, the as‐prepared smart material can produce reversible wettability changes between superhydrophobicity/superoleophilicity and superhydrophilicity/underwater superoleophobicity by adjusting various pH values. Based on this fresh phenomenon, it can be used to separate various oil/water mixtures on‐demand with high separation performance. It is worth noting that the smart fabric also separates mixtures of highly corrosive liquids and oils. Moreover, the smart fabric also has excellent self‐cleaning and low surface adhesion. In addition, it also shows excellent mechanical and chemical stability under harsh conditions. All these advantages show that the smart fabric can play a vital function in solving the related severe conditions of marine oil pollution and industrial wastewater. Abstract : A simple method to produce multifunctional super‐wetting fabric, which can switch from superhydrophobicity/superoleophilicity to superhydrophilicity/underwater superoleophobicity under different pH situations, is provided. It can separate various oil/water mixtures on‐demand with high separation performance and it can maintain excellent durability under various harsh conditions. Meanwhile, it can withstand a certain carrying capacity while floating on the water.